How Technological Development and E-Commerce Drive Economic Growth in Indonesia - Mahmud, Ahmad Kafrawi; Iwang, Baso; Kayyum, A.Muh.; Binti Sa'at, Nor Hayati (EcceS: Economics, Social, and Development Studies, 2024)
The economy is a very important thing in a country, the success of the State in controlling its economic activities can be seen in the country's economic growth rate. The purpose of this study is to determine the influence of the development index of information communication technology and E-commerce on economic growth in Indonesia. This study aims to demonstrate the impact of the correlation between the Information and Communication Technology (ICT) Development Index and E-Commerce on economic growth and increase understanding of the influence of developments in the ICT and E-Commerce domains on Indonesia's economic expansion. The variables in this study are the development index of communication, information technology, and E-commerce as independent variables and economic growth as the dependent variable. The type of research used is quantitative research with panel data analysis using the EViews10 application with the Fixed Effect Model (FEM) method. The population and sample in this study are time series data for 3 years and cross-section data for 34 provinces in Indonesia. The results show that the Information Communication Technology Development Index has a significant effect on Indonesia's economic growth in 2019-2021 which shows the direction of positive influence and E-Commerce (the percentage of businesses doing e-commerce) has a significant effect on economic growth, but shows the direction of negative influence. The impact of this research demonstrates the importance of allocating investments and policies to advance ICT development in Indonesia, which requires allocating government resources to initiatives such as infrastructure upgrades, digital literacy programs, and supportive regulatory frameworks. In addition, the research also highlights the potential to foster more inclusive economic growth through improving access to ICT tools, empowering marginalized communities, and addressing regulatory barriers to facilitate e-commerce growth in Indonesia.